Nongsa Development as A Special Economic Zone - Anwar, Jaitul; Sidabutar, Yuanita FD; Raymond, Raymond; Sitio, Rini Lisbet (JMKSP (Jurnal Manajemen, Kepemimpinan, dan Supervisi Pendidikan), 2023)
Space as a local development resource is an alternative input that is permanent and always available in an area. The focus of spatial planning and development is to create spaces that are safe, comfortable, productive, and sustainable and just, one of which is by reducing spatial exclusion and poverty. The development of Special Economic Zones (SEZ) is directed as a trigger for regional growth and development. SEZ consists of one or several Zones including: export processing, logistics, industry, technology development, tourism, energy, and/or other economies. Within the SEZ, supporting facilities can be built for workers and locations for micro, small and medium enterprises (MSMEs) and cooperatives can be built, both for business actors and as support for the activities of companies within the SEZ area. Nongsa SEZ stipulated on June 8, 2021 through Government Regulation Number 68 of 2021. This Nongsa SEZ is an area determined by the central government to be an area for carrying out economic functions and obtaining certain facilities. Where it is hoped that in 2030 it will be able to bring in investors to Batam City with an investment value of 16 trillion and absorb a workforce of 16,500 people. With the existence of this Nongsa SEZ, the Regional Government, Batam City is expected to be able to prepare both in terms of facilities and its people to compete with other countries. In addition, it is hoped that community readiness can be prepared from an early age to face the Asean Economic Community (AEC).